Development of SIMDIKSUS: A Web-Based Instrument for Identifying Children with Special Needs in Elementary Schools - Anisa Sri Rizky; Atien Nur Chamidah; Cindy Rahmi Aulia; Hanifa Muthaharah; Monika Nur Edlina (Journal of Educational Sciences, 2026)
This study aims to (1) identify the need for developing SIMDIKSUS as a website-based instrument for identifying children with special needs (ABK) for elementary school teachers and (2) produce a feasible SIMDIKSUS instrument for use in elementary schools. The study employed the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. Product feasibility was first evaluated by three material experts and three media experts, followed by a usability assessment by teachers as users. The research participants were 26 public elementary school teachers in Cijeungjing District, Ciamis Regency. Data were collected through interviews and assessment questionnaires and analyzed using qualitative descriptive analysis and descriptive statistics. The results show that SIMDIKSUS was developed based on the need for identification instruments, procedures for identifying children with special needs, and supporting materials integrated into a practical and accessible website. The evaluation results indicate that SIMDIKSUS is highly feasible for use based on assessments from material experts, media experts, and teachers.